2011
DOI: 10.1159/000325540
|View full text |Cite
|
Sign up to set email alerts
|

Satellite DNA Derived from 5S rDNA in <i>Physalaemus cuvieri</i> (Anura, Leiuperidae)

Abstract: In the present study, we describe for the first time a family of 190-bp satellite DNA related to 5S rDNA in anurans and the existence of 2 forms of 5S rDNA, type I (201 bp) and type II (690 bp). The sequences were obtained from genomic DNA of Physalaemus cuvieri from Palmeiras, State of Bahia, Brazil. Analysis of the nucleotide sequence revealed that the satellite DNA obtained by digestion with EcoRI, called PcP190EcoRI, is 70% similar to the coding region of type I 5S rDNA and 66% similar to the coding region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 54 publications
4
60
0
6
Order By: Relevance
“…In T. fosteriana , some of the numerous hybridizing signals corresponded to non-functional sites holding truncated copies of 5S rRNA genes [Mizuochi et al, 2007]. Amplified fragments of the 5S rDNA sequence, building blocks of satellite DNA apart from the sites of 5S rRNA genes, have also been reported for other species [Volkov et al, 2001;Martins et al, 2006;Vittorazzi et al, 2011] and could be the origin of such uncommon numbers of 5S rDNA signals. Excepting these cases, the number of sites per karyotype ranged from 2-20, but a little more than half of the karyotypes showed only one pair of 5S rDNA sites (online suppl.…”
Section: Number Of 5s Rdna Sites Per Karyotypementioning
confidence: 89%
“…In T. fosteriana , some of the numerous hybridizing signals corresponded to non-functional sites holding truncated copies of 5S rRNA genes [Mizuochi et al, 2007]. Amplified fragments of the 5S rDNA sequence, building blocks of satellite DNA apart from the sites of 5S rRNA genes, have also been reported for other species [Volkov et al, 2001;Martins et al, 2006;Vittorazzi et al, 2011] and could be the origin of such uncommon numbers of 5S rDNA signals. Excepting these cases, the number of sites per karyotype ranged from 2-20, but a little more than half of the karyotypes showed only one pair of 5S rDNA sites (online suppl.…”
Section: Number Of 5s Rdna Sites Per Karyotypementioning
confidence: 89%
“…One of them is localized in chromosome 3 consisting of type I 5S rDNA arrays, and the signals detected in chromosomes 9 and 13 corresponded to arrays of type II 5S rDNA [Martins et al, 2002]. In the anuran species, Engystomops freibergi and P. cuvieri , 2 sites of 5S rDNA were observed in the genomes [Vittorazzi et al, 2011;Rodrigues et al, 2012]. In E. freibergi , arrays in 3p preferentially constituted type I 5S rDNA, and arrays in 6q were related to type II 5S rDNA [Rodrigues et al, 2012].…”
Section: Two Types Of 5s Rdna Array Tandemly Arrangedmentioning
confidence: 99%
“…In the fish Oreochromis niloticus , type I 5S rDNA was found in chromosome 3, while type II 5S rDNA was detected in chromosomes 9 and 13 [Martins et al, 2002]. In the anurans, although studied to date in very limited groups, i.e., P. cuvieri and Engystomops species, it was demonstrated that different classes of 5S rDNA are separately assigned to distinct chromosome loci [Vittorazzi et al, 2011;Rodrigues et al, 2012]. The fact that the 5S rRNA genes are distributed at several chromosomal loci, previously detected in both fishes and amphibians, seems to be associated with the different classes of 5S rDNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also in animals some cases have been reported, such as the fish Hoplias malabaricus , in which a satellite DNA with high similarity to 5S rDNA was found in the centromeric regions of various chromosomes, suggesting that this satellite DNA originates from the 5S rDNA [Martins et al, 2006]. Similarly, centromeric satellite DNA derived from the 5S rDNA, probably by gene duplication and nucleotide divergence, was reported for the amphibian Physalaemus cuvieri [Vittorazzi et al, 2011].…”
Section: Discussionmentioning
confidence: 91%